Analisis Teknik Smash Bola Voli pada Klub Sehase Kota Lubuklinggau - Riansyah Gumay; Yohana Satinem; Ever Sovensi (e-SPORT: Jurnal Pendidikan Jasmani, Kesehatan dan Rekreasi, 2022)
This study aims to describe the volleyball smash technique at the SEHASE club, Lubuklinggau City. This research belongs to the type of qualitative descriptive research. They collect data in this study using interviews, observation, and documentation techniques. The study's data sources were 12 people who did the exercises at the SEHASE Club, Lubuklinggau City. After the data is collected, the information is observed directly. The results of this study indicate that the volleyball smash technique is seen from the aspects of the initial stage, the jumping stage, and the stage when hitting the ball. In the SEHASE Club Lubuklinggau City landing stage, the average volleyball smash technique of the athletes was appropriate from 12 participants who took the observation, interview, and documentation test. In a theoretical study where seven people have done the movement correctly, five more people are still wrong in doing the jumping stage. In conclusion, the smash technique performed by some of the training participants at the SEHASE club is correct, and following the theory, Keywords: Volleyball Smash Technique, SEHASE Club Athlete Lubuklinggau